(untitled) (Academia Journal of Medicine, 2021)
Esophageal candidiasis is more commonly presented in persons with immunocompromised conditions but it can also be seen in immunocom petent patients. There has been an epidemiological shift towards the predominance of candida spp. other than C.albicans such as C. glabrata C. parapsilosis, C. krusei, C. tropicalis, C. dubliensis etc. accounting for more than 50% of the Candida infections. The rampant misuse of antifungals has increased the antifungal resistance among C.albicans as well as non-albicans species and poses a challenge to clinicians for the management of such cases. The current study was aimed to understand the isolation of various Candida spp. in patients diagnosed with esophageal candidiasis attending a tertiary care center in western U.P. and to analyse its association with various predisposing factors. This study also extends to determine the susceptibility pattern of the isolated candida spp. against different antifungal agents. The study was conducted for 3 years in the hospital of western U.P. North India from July 2017 to June 2020. Candidial esophagitis was suspected when in endoscopy, whitish plaques are seen attached to the mucosa and these plaques were collected using biopsy forceps and sent to the microbiology laboratory for its fungal culture and speciation. In the current study, 60.1% were Candida albicans while 39.9% were other candida spp. Among NAC, the commonest species was C. parapsilosis (14.1%) followed by C. dubliensis (9.2%), C. glabrata (8.6%), C. tropicalis (4.9%) and C. krusei (3.1%). All isolates were found sensitive to AmphotericinB, however 3.1% of the isolates were resistant to Voriconazole and 7.4% to fluconazole. Fluconazole resistance is a serious issue as it is considered the drug of choice in cases with esophageal candidiasis. Such studies help clinicians to select appropriate antifungals for these patients and reduces patient’s morbidity and mortality.